The Impact of Hybrid Learning Models on Student Competence and Achievement in Higher Education - Rieneke Ryke Kalalo; Andi Nurfaizah; Selviyanti Kaawoan; Eka Pravitasari Putri; Viviana Lisma Lestari (EDUJAVARE: International Journal of Educational Research, 2026)
The development of information and communication technology (ICT) has brought significant changes to various sectors of life, including higher education. This study aims to analyze the impact of the hybrid learning model on student competency and achievement in higher education. The hybrid learning model is a combination of face-to-face and online learning designed to increase the flexibility and effectiveness of the learning process. The research method used is a quantitative approach with an explanatory design. The research sample was determined using a purposive sampling technique with the criteria of students who have participated in hybrid learning for at least one semester. Data collection was carried out using a Likert scale questionnaire to measure student competency (cognitive, affective, and psychomotor), and documentation of academic grades to measure learning achievement. Data were analyzed using descriptive and inferential statistics, specifically multiple linear regression tests, after first undergoing validity, reliability, and classical assumption tests. The results showed that the hybrid learning model had a positive and significant effect on student competency and achievement. Hybrid learning was able to improve conceptual understanding, learning independence, and skills in using digital technology. In addition, there was an increase in students' academic grades after implementing this learning model. However, this study also found several obstacles, such as limited technological infrastructure and differences in digital literacy levels.